Crystallization of polymethoxyflavones in high internal phase emulsions stabilized using biopolymeric complexes: Implications for microstructure and in vitro digestion properties. (April 2021) - Wijaya, Wahyu; Zheng, Huijuan; Patel, Ashok R.; Van der Meeren, Paul; Huang, Qingrong
Abstract: Polymethoxyflavones (PMF) are a group of flavonoids isolated from citrus peels that show crystallization properties. The purpose of this study was to investigate the impact of PMF crystallization on the microstructure, stability and bioaccessibility of PMF-loaded high internal phase emulsions (HIPE) stabilized using protein and polysaccharide complexes. To improve the loading capacity of PMF, a HIPE stabilized using biopolymeric complexes was developed as a container for PMF at concentrations ranging from 1 to 4%. At supersaturation, low-density crystals remained dispersed throughout the HIPE while high-density crystals formed a three-dimensional network that disrupted the oil-in-water interface. Based on the microstructure and the rheological studies, the density of the crystals affected the stability properties. The storage temperature significantly influenced the stability of the PMF-containing HIPE system. The simulated lipolysis study showed that the bioaccessibility of crystalline PMF in a HIPE stabilized using protein-polysaccharide complexes was lower than that of solubilized PMF, indicating that the dissolution of PMF could significantly affect their bioaccessibility with simulated digestion conditions. To conclude, crystal formation in a lipid-rich delivery system affected the stability during storage, as well as the dissolution with simulated digestion condition. Graphical abstract: Image 1 Highlights: PMF crystallizes in MCT oil and in HIPE-complexes. PMF crystals grew rapidly at supersaturated concentration at high temperature. PMF crystallization affected the stability and rheological properties of HIPE. Large PMF crystals in the HIPE reduced the bioaccessibility of PMF.